Laboratory Magnetoplasmas as Stellar-like Environment for 7Be β-Decay Investigations Within the PANDORA Project - Eugenia Naselli; Bharat Mishra; Angelo Pidatella; Alessio Galatà; Giorgio S. Mauro; Domenico Santonocito; Giuseppe Torrisi; David Mascali (Universe, 2025)
Laboratory magnetoplasmas can become an intriguing experimental environment for fundamental studies relevant to nuclear astrophysics processes. Theoretical predictions indicate that the ionization state of isotopes within the plasma can significantly alter their lifetimes, potentially due to nuclear and atomic mechanisms such as bound-state β-decay. However, only limited experimental evidence on this phenomenon has been collected. PANDORA (Plasmas for Astrophysics, Nuclear Decay Observations, and Radiation for Archaeometry) is a novel facility which proposes to investigate nuclear decays in high-energy-density plasmas mimicking some properties of stellar nucleosynthesis sites (Big Bang Nucleosynthesis, s-process nucleosynthesis, role of CosmoChronometers, etc.). This paper focuses on the case of 7Be electron capture (EC) decay into 7Li, since its in-plasma decay rate has garnered considerable attention, particularly concerning the unresolved Cosmological Lithium Problem and solar neutrino physics. Numerical simulations were conducted to assess the feasibility of this possible lifetime measurement in the plasma of PANDORA. Both the ionization and atomic excitation of the 7Be isotopes in a He buffer Electron Cyclotron Resonance (ECR) plasma within PANDORA were explored via numerical modelling in a kind of “virtual experiment” providing the expected in-plasma EC decay rate. Since the decay of 7Be provides γ-rays at 477.6 keV from the 7Li excited state, Monte-Carlo GEANT4 simulations were performed to determine the γ-detection efficiency by the HPGe detectors array of the PANDORA setup. Finally, the sensitivity of the measurement was evaluated through a virtual experimental run, starting from the simulated plasma-dependent γ-rate maps. These results indicate that laboratory ECR plasmas in compact traps provide suitable environments for β-decay studies of 7Be, with the estimated duration of experimental runs required to reach 3σ significance level being few hours, which prospectively makes PANDORA a powerful tool to investigate the decay rate under different thermodynamic conditions and related charge state distributions.